2021
DOI: 10.1007/s40964-021-00208-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of viscosity and density models for improved numerical analysis of melt flow dynamics in the nozzle during extrusion-based additive manufacturing

Abstract: Fused Filament Fabrication (FFF) is an Additive Manufacturing (AM) process that builds up a part via layer by layer deposition of polymeric material. The purpose of this study is to implement viscosity and density models for improving the assessment of melt flow behavior inside the nozzle during deposition. Numerical simulations are carried out for different combinations of important process parameters like extrusion velocity Ve, extrusion temperature Te, and filament material (Acrylonitrile Butadiene Styrene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Since the dynamic viscosity determines the printability of the material, the material becomes more printable as the temperature increases. In their studies on the parameters for optimal extrusion, Mishra et al [ 22 ] and Gopi et al [ 23 ] came to similar conclusions as in the present study. According to Duty et al [ 19 ], the material can be successfully deposited if the calculated pressure drop (Δp needle tip ) is less than the maximum system pressure for a given flow rate (Q).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since the dynamic viscosity determines the printability of the material, the material becomes more printable as the temperature increases. In their studies on the parameters for optimal extrusion, Mishra et al [ 22 ] and Gopi et al [ 23 ] came to similar conclusions as in the present study. According to Duty et al [ 19 ], the material can be successfully deposited if the calculated pressure drop (Δp needle tip ) is less than the maximum system pressure for a given flow rate (Q).…”
Section: Discussionsupporting
confidence: 89%
“…This low strength could be related to the pore size of the scaffold of 1922.77 ± 10.76 µm. Seidenstuecker et al [ 31 ], Han et al [ 32 ], and Ai et al [ 22 ] showed in their studies that the optimum pore size for better mechanical properties is between 160–500 µm. Both honeycomb structures show higher maximum failure load and have higher compressive strength compared to the scaffolds with line filling.…”
Section: Discussionmentioning
confidence: 99%
“…The viscosity of the hydrogels decreases by increasing the shear rate by two to three orders of magnitude, making them suitable for injection and self-healing [ 54 ]. The viscosity values are also within the applicable range for extrusion through nozzles [ 55 ]. The effect of AuNPs is distinguishable at relatively low shear rates (<3 s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of shear rate and temperature on viscosity are considered in this 6-parameter model. This model, like the Bird-Carreau model, accounts for both Newtonian and shear thinning [19]. The generic Cross equation is used to simulate the shear thinning component, which is a common and older alternative to the Bird-Carreau-Yasuda model [19]:…”
Section: Cross Wlf-modelmentioning
confidence: 99%
“…The well-known form of the Cross model can be expressed as Eq. ( 13) if the infinite shear rate viscosity is insignificant [19].…”
Section: Cross Wlf-modelmentioning
confidence: 99%